Fast-printed, large-area and low-cost terahertz metasurface using laser-induced graphene. (February 2022) - Wang, Zongyuan; Wang, Guocui; Hu, Bin; Liu, Weiguang; Huang, Jianzhou; Xiong, Chenjie; Zhang, Yan; Liu, Juan; Wang, Yongtian
Abstract: Terahertz (THz) technology has made promising progress and attracted wide interests in the fields of communications, security, agriculture, and biological sciences. However, the lack of modulation materials and the great challenge of the miniaturized system have become the huge restriction of this technology. Although artificial metamaterials have shown impressive electromagnetic performances in this band, they suffer complicated and high-cost fabrication processes. In this work, we find that due to the high conductivity, laser-induced graphene (LIG) can be applied in THz wave modulation. A LIG metasurface fabrication system is developed based on a nanosecond laser, a telecentric scan lens, and scanning mirrors. Owing to the ultra-small focal spot (≤5 μm) realized by the telecentric scan lens and the fast-scanning speed of the mirrors, a LIG-based THz metasurface with the size of 15 mm × 15 mm, and the resolution of 30 μm can be fabricated in 34 s. In addition, THz optical parameters of LIG are measured. It is anticipated that this fast-fabricating, large-area, and low-cost method may open up a brand-new way to develop THz devices. Graphical abstract: Image 1 Highlights: A telecentric scan lens based LIG-fabrication setup with a resolution of 30μm and an area of 18mm×18mm is designed. LIG optical parameters in the THz band are obtained by THz time-domain spectroscopies. LIG-based THz metasurfaces are proved. Fabrication time of a metasurface with an area of 15mm×15mm is within 34s.